2016
DOI: 10.1074/jbc.m115.688762
|View full text |Cite
|
Sign up to set email alerts
|

Fumarate and Succinate Regulate Expression of Hypoxia-inducible Genes via TET Enzymes

Abstract: The TET enzymes are members of the 2-oxoglutarate-dependent dioxygenase family and comprise three isoenzymes in humans: TETs 1-3. These TETs convert 5-methylcytosine to 5-hydroxymethylcytosine (5-hmC) in DNA, and high 5-hmC levels are associated with active transcription. The importance of the balance in these modified cytosines is emphasized by the fact that TET2 is mutated in several human cancers, including myeloid malignancies such as acute myeloid leukemia (AML). We characterize here the kinetic and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
204
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(226 citation statements)
references
References 38 publications
5
204
2
3
Order By: Relevance
“…Compared to progenitors, αKG concentration was vastly higher in BAT or differentiated brown adipocytes at day 3, while citrate content only slightly differed between progenitor cells and BAT (Figure 4A, 4B). Thus, αKG, due to its very low concentration (WT: 14.15 ± 2.2 µM at day 0; 33.49 ± 6.1 µM at day 3), likely is the rate limiting factor hindering TET-mediated DNA demethylation in progenitor cells considering αKG Km for TETs is around 50–60 µM (Laukka et al, 2016) (Figure 4A). We further compared metabolite contents between WT and Prkaa1 −/− cells and found that αKG was reduced due to Prkaa1 KO (Figure 4C), which was confirmed by chemical analysis (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to progenitors, αKG concentration was vastly higher in BAT or differentiated brown adipocytes at day 3, while citrate content only slightly differed between progenitor cells and BAT (Figure 4A, 4B). Thus, αKG, due to its very low concentration (WT: 14.15 ± 2.2 µM at day 0; 33.49 ± 6.1 µM at day 3), likely is the rate limiting factor hindering TET-mediated DNA demethylation in progenitor cells considering αKG Km for TETs is around 50–60 µM (Laukka et al, 2016) (Figure 4A). We further compared metabolite contents between WT and Prkaa1 −/− cells and found that αKG was reduced due to Prkaa1 KO (Figure 4C), which was confirmed by chemical analysis (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Nev er the less, hy poxia stim u lates tu mor growth ad van tage also by de creas ing the ac tiv ity of TET (oxy gen de pen dent ten eleven translo ca tion en zymes) demethy lases, lead ing to re duced tran scrip tion of on co sup pres sor genes [43,44]. In deed, se vere hy poxia (0.5% O ) de creased the ac tiv ity of TET en zymes in sev eral mouse and hu man cell lines [44].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…For example, mutations in the TCA cycle gene encoding isocitrate dehydrogenase (IDH) cause an over-production of the onco-metabolite 2-hydroxyglutarate, which contributes to glioma formation and leukemogensis [24, 25]. And, succinate dehydrogenase (SDH) or fumarate hydratase (FH) mutations also cause accumulation of the TCA cycle metabolic intermediates, succinate and fumarate, that activate hypoxia-inducible factor 1 alpha (HIF-1α), which promotes cancer cell growth and survival [2629]. Moreover, mutations in genes encoding complex III components of electron transport chain impair apoptosis, thus contributing to tumor progression [30].…”
Section: Introductionmentioning
confidence: 99%